“I can read, I just can't see”: a disability rights-based perspective on reading by listening - Lundh, Anna (2022)
Purpose: The aim of the paper is to create a greater understanding of how people who are blind or vision impaired describe their use of audio-based reading technologies, with a particular focus on how they reason about whether the use of these technologies can be understood in terms of reading.